2012
DOI: 10.1002/cncr.26185
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood‐level socioeconomic determinants impact outcomes in nonsmall cell lung cancer patients in the Southeastern United States

Abstract: BACKGROUND: Studies examining the impact of lower socioeconomic status (SES) on the outcomes of patients with nonsmall cell lung cancer (NSCLC) are inconsistent. The objective of this study was to clearly elucidate the association between SES, education, and clinical outcomes among patients with NSCLC. METHODS: The study population was derived from a consecutive, retrospective cohort of patients with NSCLC who received treatment within the Duke Health System between 1995 and 2007. SES determinants were based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 21 publications
6
54
3
Order By: Relevance
“…The positive coefficient for ADI suggests that greater possibility of liver cancer prevalence would be expected in districts of high social deprivation. It supports prior findings in developed countries that higher cancer prevalence is more likely to occur in highly deprived places (Anne et al 2011;Cramb et al 2012;Erhunmwunsee et al 2012;Hystad et al 2013). For example, area deprivation is associated with lung cancer incidence in Sweden (Li et al 2015) and Canada (Hystad et al 2013).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The positive coefficient for ADI suggests that greater possibility of liver cancer prevalence would be expected in districts of high social deprivation. It supports prior findings in developed countries that higher cancer prevalence is more likely to occur in highly deprived places (Anne et al 2011;Cramb et al 2012;Erhunmwunsee et al 2012;Hystad et al 2013). For example, area deprivation is associated with lung cancer incidence in Sweden (Li et al 2015) and Canada (Hystad et al 2013).…”
Section: Discussionsupporting
confidence: 87%
“…The notion ''area'' to define deprivation quantitively is vague and refers to a geographic unit. It can mean ''neighborhood'' (Pearce et al 2007;Erhunmwunsee et al 2012;Brennan-Olsen et al 2015) or ''region'' (Kuznetsov et al 2011;Yuan and Wu 2013;Grintsova et al 2014). And it is usually identified according to administrative division or creating zones with different characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, living in areas with lower educational attainment was associated with lower odds of receiving surgery and high risk of death for white patients, but not for black patients. Erhunmwunsee and colleagues (54) and Shugarman and colleagues (55) both found that living in areas with low SES was associated with poorer survival outcomes for lung cancer patients. We deconstructed SES into three primary components: economic, educational, and demographic.…”
Section: Cancer Epidemiol Biomarkers Prev; 25(5) May 2016mentioning
confidence: 99%